FASIES BATUBARA FORMASI WARUKIN BERDASARKAN ANALISIS CORE DI DAERAH SUNGAI DIDI, KECAMATAN DUSUN TIMUR, KABUPATEN BARITO TIMUR KALIMANTAN TENGAH - Yuniardi, Yuyun (Fakultas Teknik Geologi Universitas Padjadjaran, 2005)
Research area layed on Sungai Didi, Dusun Timur District, Barito Timur Residence, KalimantanTengah Province. The border in geographically, 1150 11’ 1,22” – 1150 12’ 35” East Longitude and 20 2’27,93” – 20 3’ 28,74” South Latitude.Geology of research area consisted of two rock units, there were sandstone unit and claystone unit.Claystone unit consisted of claystone with alternated by coal, and then sandstone unit consisted ofsandstone which have coarse grain to fine grain. Both of those units were related with WarukinFormation, where formed at fluviatil environment with Middle Miosen of age.Research area facies would have four kinds and made into the group, there were MS (massivesandstone), FS (fining upward sandstone), CL (claystone) and Co (coal). Facies model which made haveconsisted of MS facies in lowers followed with FS facies, and then CL facies and Co in uppers.Keywords : Warukin Formation, Fluviatil, Facies